Efektivitas Pengalaman Kerja, Pelatihan Kerja, dan Pengembangan Karir Terhadap Produktivitas Kerja Pegawai Pengadilan Negeri Boyolali Kelas 1B - Winda Saputri; Khabib Alia Akhmad; Indra Hastuti (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
This research aims to analyze whether job training, work experience and career development influence work productivity at the Class 1B Boyolali District Court. The population of this study were all employees at the District Court 1 Bpyplali class 1B. The number of samples used in this research was 40 respondents. The variables used in this research are job training, work experience, career development and work productivity. The method used is a quantitative method. Data analysis techniques use SEM-PLS and SmartPLS 4.0. The results of this research show that job training has a positive and significant effect on work productivity, work experience has a positive and significant effect on work productivity, career development has a positive and significant effect on work productivity.